DESKRIPTIF LITERATUR REVIEW : PERANAN PEKERJA SOSIAL DALAM PEMBENTUKAN KEMANDIRIAN PENYANDANG DISABILITAS - Farizal Hami; Hastin Trustisari (JURNAL ILMIAH NUSANTARA, 2024)
This study aims to examine the role of social workers in building the independence of people with disabilities using descriptive methods. By analyzing various relevant literature, this study identifies and evaluates the strategies and interventions implemented by social workers to support the independence of people with disabilities. The results of this study show that social workers play an important role in many aspects of the lives of people with disabilities, including education, skills training, psychosocial support, and economic empowerment. People with disabilities receive benefits such as support, advocacy and facilitation provided by social workers in efforts to help them. The approaches used include counseling, advocacy and community empowerment. This study concludes that social work interventions can contribute significantly to encouraging the independence and active participation of people with disabilities in society.